The Effect of Social Class to Discriminations in Burger’s Daughter by Nadine Gordimer - Muhammad Yudi Kurniawan; Waladdin Panggabean; Adi Prautomo (Prologue: Journal on Language and Literature, 2022)
This research explores the effect of social class to discrimination on Burger’s daughter Novel by Nadine Gordimer. There are two objectives of this research; 1) to find out the forms of social class found in Burger’s daughter Novel by Nadine Gordimer, 2) to describe the effect of social class affect discriminations in the novel. The theory used in this research is Marxist theory of social class and Discrimination theory; the methodology employed is qualitative research in which the researcher tried to present the issues descriptively. As for the data, the researcher collected from the quotation of the novel. The novel quotations were taken out as the primary data. The results of this research, the researcher found the form of social class in Burger's daughter novel is the bourgeoisie, the proletariat, the middle class, and the ruling class, the bourgeoisie being the most dominating class and the effect of social class that affects discrimination is the Restriction of Political Rights which is discrimination that dominates, then there are other discriminations such as Violence against black, White Privileges, Injustice of law, Labor Exploitation, Sexual Harassment, Separation of Settlement, and Education Inequality